Application of the generalized matching law to point-after-touchdown conversions and kicker selection in college football. (September 2016) - Falligant, John Michael; Boomhower, Steven R.; Pence, Sacha T.
Abstract: Coaches make a variety of complex decisions in American-rules college football, especially related to point-after-touchdown (PAT) conversions and, historically, kicker selection. However, little research has characterized the pattern of these choices and whether they are sensitive to environmental manipulations, such as increased effort to score. In the present study, the generalized matching law (GML)—a model that predicts a linear relation between log-transformed choices for two alternatives and the amount of reinforcement garnered from them—was applied to PAT-conversion (1 point vs. 2 point) and kicker (soccer-style vs. conventional-style) selection using archived data from the National Collegiate Athletic Association. Overall, PAT-conversion and kicker selection exhibited matching. Further, narrowing the goal-post width was associated with decreased preference for one-point (relative to two-point) PAT attempts and enhanced sensitivity to increases in points scored from one-point (relative to two-point) PAT attempts. This investigation provides support for the ecological validity of the GML and demonstrates that complex decisions in football conform to an orderly pattern that can be described using the GML. Highlights: The generalized matching law accurately described coaches' play selections in college football. Narrowing the goal posts following a rule change was associated with increases in sensitivity and an elimination in bias. The generalized matching law also described coaches' selections for soccer-style and conventional-style field goal kickers. The generalized matching law contributes to the ecological model of decision-making in sports psychology.